The Impact of Individual Investoras Perceptions on Perceived Self Efficacy while Trading Internationally (Global Journal of Management and Business Research, 2015)
Trends are changing and reshaping rapidly and effectively in individual and company business nationally and internationally. How to overcome financial crisis positively is a major concern? This research explains how the individual investor's insights change and constrain trading and risk enchanting behavior through the financial disaster. Examine and find how investor insights vary significantly during the crisis, with risk acceptance and risk awareness being less explosive than return outlook? During the worst months of the crisis, investors' return expectations and risk tolerance, decrease, while their risk perceptions increase. Individual investors carry on to trade actively and do not take any risk in savings portfolios during the crisis. Self usefulness pertains to optimistic thoughts to deal with the large stressors.
Keywords: self efficacy; investors; investment; trading